Neonatal sepsis: Diagnosis and treatment - Vega-Fernández, Amalia Guadalupe (2023)
Neonatal sepsis is a major cause of morbidity and mortality. The WHO reports that 2.4 million babies die annually during the first month of life, with neonatal sepsis being one of the main causes. The objective is to update the diagnosis and treatment of neonatal sepsis. In this research, a review of the literature was carried out to synthesize relevant findings on neonatal sepsis, which is defined as a systemic condition, characterized by hemodynamic changes and other clinical manifestations, as a deregulated response to infection. Early-onset neonatal sepsis is related to maternal risk factors and the causative microorganisms are from the maternal genitourinary tract, while late-onset sepsis is caused by nosocomial germs, in neonates with prolonged hospital stay and subjected to invasive procedures. The signs and symptoms of neonatal sepsis are nonspecific, which makes its diagnosis difficult, it is recommended to identify risk factors and a thorough clinical evaluation. Health establishments must carry out epidemiological surveillance of the most frequent germs and antibiotic sensitivity, to guarantee adequate antibiotic treatment.